The Effect of a Pace Training Session on Internal Load and Neuromuscular Parameters in Taekwondo Athletes - Sant' Ana, Jader; Sakugawa, Raphael Luiz; Diefenthaeler, Fernando (Frontiers in Physiology, 2021)
This study aimed to verify the effect of a pace training session at an intensity corresponding to the kick frequency at the anaerobic threshold (KFAT) on the internal load response and motor response performance of the roundhouse kick. Twelve black belt Taekwondo athletes underwent two evaluation sessions: (1) performed the Progressive Specific Test for Taekwondo (PSTT) to identify the heart rate deflection point (HRDP) and the KFAT; (2) performed three 2-min rounds with a 1-min interval. Heart rate (HR) throughout each round and motor response performance before and after sessions were measured. The Student's t-test or Wilcoxon test was used and p<0.05 was adopted. During round 1, a lower internal load was observed (167±10 bpm) compared to HRDP (179±8 bpm; p=0.035). During rounds 2 (178±10 bpm; p=0.745) and 3 (179±8 bpm; p=1), no differences were observed for internal load and HRDP. Motor response performance showed no differences. However, a potentiation in the post countermovement jump test compared to rounds 1 (p=0.012) and 2 (p=0.028) was observed. The internal load (HR) observed at the intensity corresponding to KFAT can be considered in the prescription of training when the aim is to control the internal load responses without inducing fatigue.